Aktivitas Antibakteri Sabun Padat dari Ekstrak Air Rimpang Kunyit (Curcuma domestica) terhadap Staphylococcus aureus - Milda Lailatul Mukarromah; Wahyu Wuryandari; Dinda Ayu Andini; Tri Dewi Indah Wulandari (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Turmeric (Curcuma domestica) contains flavonoids and curcumin, which exhibit antibacterial properties, making it a suitable active ingredient for solid soap production. Solid soap must pass physical, chemical, and antibacterial activity assessments to ensure quality. This study evaluates the physical, chemical, and antibacterial properties of turmeric rhizome water extract-based solid soap against Staphylococcus aureus. The research was conducted experimentally, using turmeric rhizome water extract obtained through the maceration method. Antibacterial activity was assessed using the well diffusion method. The solid soap was formulated through saponification, incorporating thick extract (F1) and liquid extract (F2) of turmeric rhizome as active ingredients. Findings indicate that soap F1 has a solid texture, odourless, brown, and homogeneous, with a foam height of 13.63 cm±0.35, a moisture content of 7.52%±0.37, a pH of 10.03±0.05, a free alkali of 0.094%±0.008, and an inhibition zone diameter of 22.38 mm±0.58, classified as very strong antibacterial. Soap formulated F2 demonstrated comparable characteristics, with an 18.60 mm±0.96 inhibition zone, categorised as strong antibacterial. The soap F1 complies with pharmaceutical standards and effectively inhibits Staphylococcus aureus growth.